Studying of Frequencies, Normal Modes of Vibration and Electronic Charge Densities of 5Radialene molecule - Kubba, Rehab; Samawi, Khalida (Iraqi Journal of Science, 2024)
PM3 and DFT (6-311G/ B3LYP) level calculations were carried out for the 5Radialene molecule, which is exhibit D5h symmetry. The obtained equilibrium geometry was applied for the calculation of all 3N−6 vibration frequencies, and for the analysis of its normal coordinates and symmetry species, in addition to some physical properties such as heat of formation, total energy, dipole moment and energy difference of HOMO and LUMO levels (ΔELUMO-HOMO), using Gaussian-03 program. The so calculated frequencies according to DFT (6-311G/ B3LYP) fall in the ranges;CH2 str. (3016-3098 cm-1), C=C str. (1662-1709cm-1), ring (C-C str.) (1268-1464 cm-1). δCH2 (890-1317cm-1), (δCCC) (562-631cm-1), γCH2 (738-946cm-1) and γring (γCCC) (14-805cm-1), and according to PM3 fall in the ranges;CH2 str. (3124-3138cm-1), C=C str. (1873-1939cm-1), ring str. (C-C str.) (1289-1430cm-1). δCH2 (946-1503cm-1), (δCCC) (549-777cm-1), γCH2 (673-1007cm-1) and γring (γCCC) (54-785cm-1).Other interesting correlations were also be obtained for the frequencies of similar vibrations. Distribution of electronic charge density on atoms of 5Radialene molecule were also calculated and studied.